Country specific associations between social contact and mental health: evidence from civil servant studies across Great Britain, Japan and Finland. (August 2016) - Cable, N.; Chandola, T.; Lallukka, T.; Sekine, M.; Lahelma, E.; Tatsuse, T.; Marmot, M.G.
Abstract: Objectives: Little is known about which component, such as social contact of social networks is associated with mental health or whether such an association can be observed across countries. This study examined whether the association between frequent social contact and mental health differs by composition (relatives or friends) and whether the associations are similar across three occupational cohorts from Great Britain, Japan, and Finland. Study design: Cross-sectional analysis of data from three prospective cohort studies. Methods: Participants were civil servants of a prospective cohort study based in London (Men: n  = 4519; Women: n  = 1756), in the West Coast of Japan (Men: n  = 2571; Women: n  = 1102), and in Helsinki, Finland (Men: n  = 1181; Women: n  = 5633); we included the information on study variables which is complete. Mental health function was the study outcome, indicated by the total score from the Mental Health Component on the Short Form Health Survey36. Participants reported frequencies of contacts with their relatives or friends via a questionnaire. Age, marital status, and occupational position were treated as confounders in this study. Results: Findings from multiple regression showed that the associations between social contact and mental health function were different depending on country of origin and gender. Among British or Japanese men, frequent contact with both friends and relatives was positively associated with their mental health function, while only social contact with friends was significantly associated with mental health of Finnish men. In women, the patterns of the associations between social contact and mental health were more distinctive: friends for Great Britain, relatives for Japan, and friends and relatives for Finland. These significant associations were independent of the confounders. Conclusions: Social contact was related to mental health of working people; however, culture and gender are likely to be tapped into. Highlights: Social contact associates with mental health differently by country and gender. Importance of contact with friends on mental health was noted among Europeans. Contact with relatives was associated with mental health of Japanese. Contact with relatives was also associated with some Europeans' mental health. Application of social network related indices has to be well thought out.